2000
DOI: 10.1093/humrep/15.12.2653
|View full text |Cite
|
Sign up to set email alerts
|

The effect of intercourse on pregnancy rates during assisted human reproduction

Abstract: Intercourse during an IVF cycle has the potential to improve pregnancy rates since exposure to semen is reported to promote embryo development and implantation in animals. Conversely, coitus-induced uterine contractions or introduction of infection may have a detrimental effect. A multicentre prospective randomized control trial was conducted to determine if intercourse during the peri-transfer period of an IVF cycle has any influence on pregnancy success. Participants undergoing thawed embryo transfer (Austra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
86
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(89 citation statements)
references
References 30 publications
1
86
0
1
Order By: Relevance
“…More recently this work has been carried over into the human ART program. It has been shown that semen exposure around the time of embryo transfer increases the rates of embryo implantation and possible subsequent foetal development [5,115,116]. Bellinge et al has previously shown that seminal exposure as early as the time of oocyte retrieval can increase the incidence of pregnancy in women undergoing IVF [117].…”
Section: Seminal Plasma and Assisted Reproductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently this work has been carried over into the human ART program. It has been shown that semen exposure around the time of embryo transfer increases the rates of embryo implantation and possible subsequent foetal development [5,115,116]. Bellinge et al has previously shown that seminal exposure as early as the time of oocyte retrieval can increase the incidence of pregnancy in women undergoing IVF [117].…”
Section: Seminal Plasma and Assisted Reproductionmentioning
confidence: 99%
“…Thus it appears that seminal factors act primarily to optimise the likelihood of successful pregnancy. This has been supported by studies showing the addition of seminal plasma or seminal factors to assisted reproductive procedures can markedly improve pregnancy success in mice, rats, hamsters, sheep and humans [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…However, advice against intercourse around the time of embryo transfer is not typically given because it might have a positive effect on the pregnancy outcome. Only two studies have investigated the effects of vaginal intercourse around the time of embryo transfer during ART cycles [17,18]. Tremellen et al reported that, in a multicenter randomized study, patients undergoing fresh (400 cycles) and frozen-thawed (200 cycles) embryo transfer were randomized either to abstain or to engage in vaginal intercourse around the time of embryo transfer.…”
Section: Discussionmentioning
confidence: 99%
“…They described an implantation rate of 80 % (35/44) in patients in the SP group, compared with one of 67 %( 29/43) in the placebo group. Tremellen et al [10] randomized patients during 478 cycles of IVF (including transfer of 1343 embryos) either to abstain from or engage in vaginal intercourse and found similar pregnancy rates (21.2 % vs 23.6 %, respectively) but a significantly higher proportion of viable embryos at 6-8 weeks of pregnancy in the group engaging in vaginal intercourse (11 % vs 7.7 %). Finally, von Wolff et al, [11] performed a pilot study, injecting cryopreserved seminal plasma from the patient's partner or sodium chloride (placebo) into the cervix and the posterior fornix of the vagina just after follicle aspiration.…”
Section: Discussionmentioning
confidence: 99%
“…SP contains a variety of factors such as Transforming Growth Factor b, [1,4], prostaglandin E and interleukin-8 [7], that may trigger a cascade of events through pro-inflammatory cytokines synthesis leading to maternal endometrial immunomodulation increasing uterine receptivity. A beneficial effect of SP as an adjunctory factor to increase implantation and clinical pregnancy rates after in vitro fertilization and embryo transfer (IVF-ET) was indicated in a few clinical studies that used variable methodologies [8][9][10][11]. Others did not corroborate these observations [12].…”
Section: Introductionmentioning
confidence: 99%